SOFTSKILL LEARNING: CHARACTER BUILDING ON ETHICAL VALUES AND PERFORMANCE - Lusy Tunik Muharlisiani; Erna Hendrawati; Endang Noerhartati; Agam Sulaksono; Johny Sugiono (Universitas Muhammadiyah Semarang, 2018)
Formation to build character in the digital era in the world of education through the development of ethical values and performance support to form the foundation of individual characters expected. Developments in the digital era influence individual lifestyles and patterns of relationships so as to form a new paradigm for helping human needs in carrying out the duties and expectations. The purpose of building character besides having benefits also have a negative impact can be described in the attitudes and behavior of individuals, which occurs demoralization. The method used in building individual character that balance the mind / creativity, feeling / sense of, and willingness / intention in executing their daily duties. The result is an imbalance in the event over them in carrying out daily activities using irrational thoughts, dishonest, irresponsible, did not have a good work ethic. How to cope with the character education should play an active role in shaping the students to have a good character, capable of being honest, responsible, disciplined, passionate, creative and communication skills to achieve success both socially and career aligned with technology development is very fast and sophisticated. The characters develop their conclusion to follow up the results of studies showing that the majority of a person in carrying out daily activities always use excessive feelings so that there is an imbalance between thought, feeling and will Keywords: Soft skill, Character Building, Ethical Values, and Performance